The Effect of Profitability, Leverage, Fixed Asset Intensity, Company Size, and Company Age Partially on Tax Avoindance - Nur Inda Wulandari; Heni Agustina; Djoko Soelistya (GREENOMIKA, 2024)
This study aims to analyze the effect of profitability, leverage, fixed asset intensity, company size, and company age partially on tax avoidance. This research is a type of quantitative research. The research population is food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sample of this study was 33 companies selected by purposive sampling method. While the data analysis method used is multiple linear regression analysis with normality test steps, multicollinearity test, heteroscedasticity test, autocorrelation test, linear regression test, and hypothesis testing. Based on this research, the following results were obtained: 1) profitability has a positive and significant effect on tax avoidance. 2) leverage has no effect on tax avoidance. 3) fixed asset intensity has no effect on tax avoidance. 4) company size has a positive and significant effect on tax avoidance. 5) company age has a negative and significant effect on tax avoidance.